Bong-Han Corpuscles as Possible Stem Cell Niches on the Organ-Surfaces - Min Su Kim; Ju-Young Hong; Su Hong; Byung-Cheon Lee; Chang Hoon Nam; Hee-Jong Woo; Dae-In Kang; Kwang-Sup Soh (Journal of Pharmacopuncture, 2008)
Objectives : Showing that Bong-Han corpuscles(BHC) are suppliers of the stem cells in adulthood, and the Bong-Han ducts(BHD) are transportation routes of stem cells. Methods : BHC and BHD were obtained from the internal organ-surfaces of rats. The sliced BHC and BHD were immunostained with various stem cell markers. Extracellular matrices were also analyzed by immunohistochemistry. Result : The presence of mesenchymal stem cells was confirmed by the expression of Integrin beta 1, Collagen type 1 and Fibronectin. But CD54 was not expressed. The hematopoietic stem cell marker, Thy 1 was strongly expressed. BHDs showed Collagen type 1, Fibronectin, and vWF expression. Conclusion : Both hematopoietic and mesenchymal stem cell markers were expressed strongly in BHC similarly as in bone marrow. An endothelial cell marker(vWF) demonstrated the possibility of the stem cell transportation routes of BHD.